2022
DOI: 10.3389/fmicb.2022.1041242
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition rate and biochemical fate of carbon from natural polymers and microplastics in boreal lakes

Abstract: Microbial mineralization of organic compounds is essential for carbon recycling in food webs. Microbes can decompose terrestrial recalcitrant and semi-recalcitrant polymers such as lignin and cellulose, which are precursors for humus formation. In addition to naturally occurring recalcitrant substrates, microplastics have been found in various aquatic environments. However, microbial utilization of lignin, hemicellulose, and microplastics as carbon sources in freshwaters and their biochemical fate and minerali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 49 publications
6
18
1
Order By: Relevance
“…Our results suggest that OM quality does not affect the biochemical fate of carbon, but it has effects on the decomposition rate, as shown previously (e.g., Krevš et al, 2017;Muto et al, 2011). Among all leaf species, 80%-88% of leaf carbon taken up was respired daily, whereas the remaining 12%-20% of utilized leaf carbon was assimilated into biomass, supporting previous studies (Attermeyer et al, 2013;Taipale et al, 2023;Vesamäki et al, 2022). The assimilated carbon can be linked to aquatic food webs via grazers feeding on microbes, microbes thus being important connectors of terrestrial and aquatic ecosystems via carbon cycling (Attermeyer et al, 2013;Taipale et al, 2023).…”
Section: The Processing and Biochemical Fate Of Terrestrial Carbon In...supporting
confidence: 92%
See 1 more Smart Citation
“…Our results suggest that OM quality does not affect the biochemical fate of carbon, but it has effects on the decomposition rate, as shown previously (e.g., Krevš et al, 2017;Muto et al, 2011). Among all leaf species, 80%-88% of leaf carbon taken up was respired daily, whereas the remaining 12%-20% of utilized leaf carbon was assimilated into biomass, supporting previous studies (Attermeyer et al, 2013;Taipale et al, 2023;Vesamäki et al, 2022). The assimilated carbon can be linked to aquatic food webs via grazers feeding on microbes, microbes thus being important connectors of terrestrial and aquatic ecosystems via carbon cycling (Attermeyer et al, 2013;Taipale et al, 2023).…”
Section: The Processing and Biochemical Fate Of Terrestrial Carbon In...supporting
confidence: 92%
“…During OM decomposition and microbial succession, the abundance and biomass of both fungi and bacteria change (Kuehn et al, 2000;Newman et al, 2015;Wardle, 1993). Although bacteria are generally considered to be more efficient in competing due to their better substrate utilization, faster population growth, and biomass production (Mille-Lindblom & Tranvik, 2003;Vesamäki et al, 2022), there has been debate about whether they actually participate in the decomposition or only assimilate leachates and byproducts of fungal decomposition (Purahong et al, 2016). Most studies suggest that fungi drive the leaf decomposition on leaves, whereas bacteria favor DOM and fine particulate organic carbon (e.g., Hayer et al, 2022;Kuehn, 2016;Zhao et al, 2017Zhao et al, , 2021.…”
Section: Om Input Strengthens Bacterial Domination In Lake Watermentioning
confidence: 99%
“…Numbers references OTU number (Table S1). Stress for 2 D MDS was 0.1. biodegradation of more recalcitrant lignin (van Erven et al, 2019;Vesamäki et al, 2022). Our results showed that easily degradable organic compounds are mainly used for energy, whereas more recalcitrant materials are preferably used as a carbon backbone for the synthesis of new biomolecules.…”
Section: Discussionmentioning
confidence: 77%
“…Conversely, we have recently revealed trophic uptake and conversion of plastic carbon to essential omega-3 (ω-3) and omega-6 (ω-6) polyunsaturated fatty acids (PUFA) (Taipale et al, 2019). This demonstrated trophic upgrading of microplastic (MP) carbon was an important finding since the persistence of MP in marine and freshwater ecosystems is an increasing environmental concern due to the predicted growth of slowly degrading plastic waste (Borrelle et al, 2020;Taipale et al, 2022;Vesamäki et al, 2022). Despite the slow process, direct utilization of some plastic blends and their leachates can support microbial biomass, complementing the trophic transfer of biomolecules (Sheridan et al, 2022;Taipale et al, 2019Taipale et al, , 2022Vesamäki et al, 2022;Yoshida et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation